Exploring the Phenomena of Online Dating Platforms Versus Saudi Traditional Spouse Courtship in the 21st Century. (22nd February 2017) - Naji Bajnaid, Ayman; Elyas, Tariq
Abstract: While traditional Saudi Arabian courtship is rigidly structured according to a set of Islamic codes of conduct, over the past decade, Saudis have increasingly turned to unconventional means of finding and courting a potential spouse: matrimonial Web sites. This research explores the debate in the literature on computer meditated communication regarding whether online settings provide rich information about other users, as they show that online interactions can provide more information about the opposite sex for users who belong to gender‐segregated societies than they can get through their offline lives. The article will shed some light on the interplay between young generations and their obsessions with the world of Internet dating and the societal norms and social conducts with which they are comfortable while living in Saudi Arabia. The article may contribute to the online dating literature by showing the similarities and differences between conservative, Islamic Saudi users and Western users when using Web sites to search for a potential mate. The research shows the power of both social and religious norms in affecting these users' behaviors and decisions when using matrimonial Web sites.